Preparation and thermal properties characterization of carbonate salt/carbon nanomaterial composite phase change material. (June 2015) - Tao, Y.B.; Lin, C.H.; He, Y.L.
Highlights: Nanocomposite phase change materials were prepared and characterized. Larger specific surface area is more efficient to enhance specific heat. Columnar structure is more efficient to enhance thermal conductivity. Thermal conductivity enhancement is the key. Single walled carbon nanotube is the optimal nanomaterial additive. Abstract: To enhance the performance of high temperature salt phase change material, four kinds of carbon nanomaterials with different microstructures were mixed into binary carbonate eutectic salts to prepare carbonate salt/nanomaterial composite phase change material. The microstructures of the nanomaterial and composite phase change material were characterized by scanning electron microscope. The thermal properties such as melting point, melting enthalpy, specific heat, thermal conductivity and total thermal energy storage capacity were characterized. The results show that the nanomaterial microstructure has great effects on composite phase change material thermal properties. The sheet structure Graphene is the best additive to enhance specific heat, which could be enhanced up to 18.57%. The single walled carbon nanotube with columnar structure is the best additive to enhance thermal conductivity, which could be enhanced up to 56.98%. Melting point increases but melting enthalpy decreases with nanomaterial specific surface area increase. Although the additives decrease the melting enthalpy of composite phase change material, they also enhance the specific heat. As a combined result, the additives have little effects on thermal energy storage capacity. So, for phase change material performance enhancement, more emphasis should be placed on thermal conductivity enhancement and single walled carbon nanotube is the optimal nanomaterial additive.